The Role of Bone Biopsy in the Management of CKD-MBD - Ferreira, AC (2022)
A bone biopsy is still considered the gold standard for diagnosis of renal osteodystrophy. It allows to measure both static and dynamic parameters of bone remodeling and is the only method able to evaluate mineralization and allows analysis of both cortical and trabecular bone. Although bone volume can be measured indirectly by dual-energy X-ray absorptiometry, mineralization defects, bone metal deposits, cellular number/activity, and even turnover abnormalities are difficult to determine by techniques other than qualitative bone histomorphometry. In this review, we evaluate the role of bone biopsy in the clinical practice.